Hole transport material and solar battery using the same

A D-A-D type hole transport material with a linear thiophene oligomer structure and tetrakis-4-methoxyphenylcarbazole groups addresses the limitations of existing materials, offering improved hole transport, durability, and efficiency in perovskite solar cells through enhanced π-conjugation and solvent compatibility.

JP2024177789AInactive Publication Date: 2024-12-24AISIN CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023096125
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-12
Publication Date
2024-12-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing hole transport materials for perovskite solar cells face challenges such as high cost, low mobility, stability issues, and decreased efficiency due to steric interference between substituent groups, which inhibit π conjugation and lead to reduced durability.

Method used

A hole transport material with a D-A-D type structure, featuring a linear thiophene oligomer as the A part and electron-donating tetrakis-4-methoxyphenylcarbazole groups at both ends, allowing for improved π-conjugation and planar molecular arrangement, enhancing intramolecular charge transfer and solubility, and incorporating alkyl groups for improved durability and solvent compatibility.

Benefits of technology

The material exhibits high hole transport performance, increased durability, and reduced light absorption, leading to enhanced solar cell efficiency and cost-effectiveness by using inexpensive synthesis methods and solvents, minimizing environmental impact.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024177789000001_ABST
    Figure 2024177789000001_ABST
Patent Text Reader

Abstract

To provide a hole transport material that stably exhibits excellent hole transport properties, to provide a hole transport material at a low price, and further to provide a solar battery with high battery performance at a low price.SOLUTION: There is provide a hole transport material that is a compound having a donor-acceptor-donor type structure represented by general formula (1) and configured as unsubstituted or substituted linear thiophene oligomer. In the general formula (1), Z represents a repeating unit of integers from 2 to 11, RA1 and RA2 each independently represent -H or a -CmH2m+1 group where m represents an integer of 1 to 12, and RA1 and RA2 may be the same or different for each of Z repeating units within ( ), and a D part is introduced at both ends of a thiophene oligomer structure. There is also provided a solar battery using the hole transport material.SELECTED DRAWING: Figure 9
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a hole transport material and a solar cell using the hole transport material. [Background technology]

[0002] Solar cells generally use elements such as silicon, compound semiconductors, and organic semiconductors, but hybrid solar cells (perovskite solar cells) are attracting attention because of their high light-collecting ability as well as the possibility of making them thin films and reducing costs.

[0003] Non-Patent Document 1 discloses a perovskite solar cell comprising a glass substrate with a transparent conductive film, a blocking layer consisting of a dense titanium dioxide (TiO2) film, a power generation layer formed by laminating lead bromide (PbBr2), lead iodide (PbI2), methylamine hydrobromide (CH5N·HBr: hereinafter sometimes abbreviated as "MABr"), and formamidine hydroiodide (CH4N2·HI: hereinafter sometimes abbreviated as "FAI") as perovskite compounds that are excited by light to generate electrons, on porous titanium dioxide (TiO2), a hole transport layer, and electrodes.

[0004] The power generation layer is a mixed halide (FAPbI3) 0.85 (MAPbBr3) 0.15 It is formed as a perovskite layer.

[0005] Conventionally, 2,2',7,7'-tetrakis(N,N'-di-p-methoxyphenylamine)-9,9'-spirobifluorene (commonly called "spiro-OMeTAD"; hereafter, this name will be used) represented by the following general formula (A) has been widely used as the hole transport material for the hole transport layer. When crystals of a perovskite compound absorb light, electrons and holes are generated. The holes are transported to the counter electrode by the hole transport material, and the electrons move to the photoelectrode, and this cycle is repeated to generate electricity.

[0006] [ka]

[0007] Although spiro-OMeTAD is commercially available and easily available, as reported in Non-Patent Document 1, spiro-OMeTAD has a problem that it is essentially difficult to reduce the cost because it requires many synthesis and purification steps. In addition, there are problems such as a relatively low hole mobility and the need for a dopant such as a cobalt complex to function efficiently and stably as a hole transport material. In addition, when spiro-OMeTAD is incorporated into a solar cell as a hole transport material, it can exhibit high initial performance, but there is a problem with the sustainability of the performance. Therefore, research is being conducted on hole transport materials that can be provided at low cost and have an efficient and stable hole transport effect.

[0008] In this regard, Non-Patent Document 1 reports a compound called LD29, which has a carbazole ring in the acceptor (hereinafter referred to as "A") portion and a triphenyldimethoxyamino group in the donor (hereinafter referred to as "D") portion, and is represented by the following general formula (B) in which these are linked to a donor-acceptor-donor type (hereinafter referred to as "DAD type") structure, as a new hole transport material. In a solar cell using such LD29 as a hole transport material, the conversion efficiency was 14.29% without dopant, but the addition of lithium bis(trifluoromethanesulfonyl)imide (hereinafter sometimes referred to as "LiTFSI"), 4-tert-butylpyridine (TBP), and a cobalt complex (FK209) as dopants improved the conversion efficiency to 18.0%, achieving a conversion efficiency comparable to that of spiro-OMeTAD.

[0009] [ka]

[0010] In LD29, in order to improve the solubility in a solvent, it is necessary to introduce a substituent into the carbazole ring constituting the A portion, and a 4-(bis(4-methoxyphenyl)amino)phenyl group is introduced as the substituent. However, by introducing such a substituent that is not involved in hole transport into a molecule, it is possible that when the molecule is used as a hole transport material to form a hole transport layer, the exchange of holes between molecules may be inhibited. This reduces the hole transport ability within the LD29 molecule, and it is assumed that it is difficult to obtain sufficient solar cell efficiency in a solar cell using LD29 as a hole transport material. In addition, the solar cell has a problem in terms of durability, such as a decrease in solar cell efficiency over time. This is thought to be due to the fact that the lithium ions contained in LiTFSI, which is added as a dopant to the hole transport material, diffuse out of the hole transport layer, and LiTFSI itself has strong hygroscopicity.

[0011] In addition, Non-Patent Document 2 reports a compound called YN1 represented by the following general formula (C), and Non-Patent Document 3 reports a compound called PTZ2 represented by the following general formula (D). Both compounds have a DAD type structure, but have the same problems as LD29 described above.

[0012] [ka]

[0013] [ka]

[0014] Thus, much research is being conducted on low molecular weight organic materials such as hole transport materials having a DAD structure. The inventors of the present application also reported in Patent Document 1 a low molecular weight organic material called DHCF-3, which is represented by the following general formula (E). It has been confirmed that such DHCF-3 stably exhibits excellent hole transport properties and functions well as a hole transport material, and when introduced into a solar cell, it exhibits good solar cell performance. Here, DHCF-3 has a fluorene ring in the A portion, a 4-(bis(4-methoxyphenyl)amino)phenyl group in the D portion, and has a structure in which the same substituent as in the D portion is introduced to the carbon at the 9th position of the fluorene ring in the A portion via a CC double bond.

[0015] [ka]

[0016] However, in the hole transport material described in Patent Document 1, the substituent of the A portion is bulky, so that the D portion on one side and the A portion are arranged sterically close to each other, and the D portion on the adjacent side is arranged more twisted relative to the fluorene ring of the A portion, which is assumed to weaken the π conjugation and inhibit the hole transport effect. [Prior art documents] [Patent documents]

[0017] [Patent Document 1] Patent Publication No. 2023-46046 [Non-patent literature]

[0018] [Non-Patent Document 1] Xuepeng Liu et al., “A star-shaped carbazole-based hole-transporting material with triphenylamine side arms for perovskite solar cells,” J.Mater.Chem.C., 2018, 6, 12912-12918 (DOI:10.1039 / c8tc04191a) [Non-Patent Document 2] Peng Xu et al., “DAD-Typed Hole Transport Materials for Efficient Perovskite Solar Cells: Tuning Photovoltaic Properties via the Acceptor Group”, ACS Appl. Mater. Interfaces 2018, 10, 23 (DOI:10.1021 / acsami.8b04003) [Non-Patent Document 3] Roberto Grisorio et al., “Molecular Tailoring of Phenothiazine-Based Hole-Transporting Materials for High-Performing Perovskite Solar Cells,” ACS Energy Lett. 2017, 2, 5, 1029-1034 (DOI:10.21 / acsenergylett.7b00054) Summary of the Invention [Problem to be solved by the invention]

[0019] In view of the above problems of the conventional technology, there is still a need to provide a hole transport material that stably exhibits excellent hole transport properties. There is also a need to provide a hole transport material at low cost. There is also a need to provide a solar cell with high cell performance at low cost. [Means for solving the problem]

[0020] The hole transport material according to the present invention has the following characteristic features: A hole transport material having a donor-acceptor-donor (DAD) structure represented by the following general formula (1): [ka] [In general formula (1), The two D regions are regions having the same structure, Each D moiety has a structure selected from the following groups (I), (II), (III), (IV), and (V): [ka] (In group (I), X and Y are each independently an integer of 0, 1, or 2. R 1 -H, -C n H 2n+1 , -OC n H 2n+1 , and -SC n H 2n+1 where n=an integer from 1 to 8; R 3 -H, -C n H 2n+1 , -OC n H 2n+1 , and -SC n H 2n+1 where n=an integer from 1 to 8; However, R 1 and R 3 cannot be -H at the same time, R 2a1 , R 2a2 , R 2b1, and R 2b2 are each independently selected from -H, -F, and -CF3, where R 2a1 and R 2a2 At least one of them is -H and R 2b1 and R 2b2 At least one of them is -H.) [ka] (In group (II), X and Y are each independently an integer of 0, 1, or 2. R 1 -H, -C n H 2n+1 , -OC n H 2n+1 , and -SC n H 2n+1 where n=an integer from 1 to 8; R 3 -H, -C n H 2n+1 , -OC n H 2n+1 , and -SC n H 2n+1 where n=an integer from 1 to 8; However, R 1 and R 3 cannot be -H at the same time, R 2a1 and R 2a2 are each independently selected from -H, -F, and -CF3, where R 2a1 and R 2a2 At least one of them is -H, R 4 -H, -C n H 2n+1 , -OC n H 2n+1 , and -SC n H 2n+1 where n is an integer from 1 to 8; Y is 1 or 2, and R 5 If exists, R 5 is introduced at the 3- or 4-position of the thiophene ring in group (II), -H and -Cn H 2n+1 where n is an integer from 1 to 8. [ka] [ka] [ka] (In group (III), group (IV), and group (V), X and Y are each independently an integer of 0, 1, or 2; The Two R's D each independently has a structure represented by the following group (I'), [ka] (In the group (I´), X' and Y' are each independently an integer of 0, 1, or 2. R 1 ´ is -H, -C n H 2n+1 , -OC n H 2n+1 , and -SC n H 2n+1 where n=an integer from 1 to 8; R 3 ´ is -H, -C n H 2n+1 , -OC n H 2n+1 , and -SC n H 2n+1 where n=an integer from 1 to 8; However, R 1 ´ and R 3 ´ is not simultaneously -H, R 2a1 ´, R 2a2 ´, R 2b1 ´, and R 2b2 are each independently selected from -H, -F, and -CF3, where R 2a1 ´ and R 2a2´ is at least one of -H and R 2b1 ´ and R 2b2 ´ At least one of them is -H. )) In general formula (1), Z is a repeating unit which is an integer from 2 to 11; R A1 and R A2 are each independently -H or -C m H 2m+1 group, where m=an integer from 1 to 12; For each Z repeating units in (), A1 and R A2 may be the same or different.

[0021] According to the above-mentioned configuration, it is possible to provide a hole transport material having excellent hole transport properties capable of stably and efficiently capturing and transporting holes. In detail, the hole transport material of this configuration has a DAD type structure, and the A part is configured as a linear thiophene oligomer structure, and the D part containing an electron donating group such as a tetrakis-4-methoxyphenylcarbazole group is introduced at both ends of the A part. By configuring in this way, the thiophene oligomer structure introduced as the A part has a planar structure, and smoothly π-conjugates with the D part introduced at both ends, so that the push-pull effect in the molecule is increased and the charge transfer property is improved. As a result, the transfer of electrons in the molecule is smooth and the charge separation of HOMO-LUMO is more clear. That is, in the hole transport material of this configuration, electrons are concentrated in the D part at the HOMO and HOMO-1 levels, and electrons are concentrated in the A part at the LUMO level. In this way, the hole transport material of this configuration can exhibit excellent hole transport properties due to the improved charge transfer property in the molecule. Furthermore, the hole transport material of this configuration has a planar structure as a whole molecule, so that each component part in the molecule is arranged in a roughly plate-like shape. Therefore, the molecules are smoothly stacked with each other, so that the transfer of holes between the molecules is smooth, and when the hole transport material of this configuration is configured as a hole transport layer, it is considered that the hole transport performance in the hole transport layer is improved. Therefore, according to this configuration, conventional technical problems such as a decrease in hole transport performance due to a decrease in π conjugation caused by steric interference between the substituent of the A portion and the D portion are solved, and a hole transport material exhibiting excellent hole transport properties can be provided.

[0022] In addition, since the hole transport material of the present configuration has a deep HOMO energy level, the arrangement with the HOMO level of the perovskite can be appropriately adjusted, which has the advantage that the hole transport properties can be improved and the solar cell efficiency can be easily improved.

[0023] The hole transport material of this configuration barely absorbs light in the visible light range, and has weak light absorption intensity in the 400 to 450 nm range. Therefore, a solar cell using the hole transport material of this configuration can minimize light absorption loss due to the hole transport material, and is expected to have high photoelectric conversion efficiency.

[0024] The hole transport material of this configuration also has excellent properties in terms of solubility in a solvent. In particular, by introducing an alkyl group as a side chain into the thiophene oligomer structure constituting the A portion, it is expected that the solubility will be particularly improved. Therefore, wet processes such as a coating method by spin coating can also be used, making it easy to form the hole transport layer of the solar cell. In addition, since the hole transport material according to this embodiment is soluble in a non-polar solvent, it is possible to prepare the hole transport layer of the solar cell using a solvent that is inexpensive and has a low environmental impact. On the other hand, in the case of spiro-OMeTAD, which has been widely used in the past, chlorobenzene is generally used as a solvent when preparing the hole transport layer. However, since chlorobenzene contains chlorine atoms in the molecule and is expensive, the cost of equipment including post-processing such as solvent disposal is high, and there is also a problem that the burden on safety and the environment due to exhaust leakage is large.

[0025] In addition, the hole transport material of the present invention can be synthesized in a short time with few synthesis steps using inexpensive raw materials, and a high purity product can be provided through a simple purification step. Therefore, it is possible to reduce the costs required for synthesis and purification without requiring expensive reagents or complicated steps, and it is possible to provide an inexpensive, high-performance hole transport material.

[0026] Furthermore, the hole transport material of this configuration is expected to have high durability because the movement of holes within and between molecules is smooth, and thus the oxidation of the molecules is suppressed. In particular, by introducing an alkyl group as a side chain into the thiophene oligomer structure constituting the A portion, the water resistance of a solar cell incorporating the hole transport material of this configuration can be further improved due to the hydrophobic effect of the alkyl group. Therefore, the durability of the solar cell can be expected to be improved.

[0027] As described above, the hole transport material of the present invention has excellent properties and can be suitably used as a hole transport material for solar cells. When the hole transport material of the present invention is used in a hole transport layer of a perovskite solar cell or the like, the cell exhibited excellent cell performance in initial experiments. [Brief description of the drawings]

[0028] [Figure 1] FIG. 1 is a schematic cross-sectional view of a perovskite solar cell. [Diagram 2] FIG. 1 is a top perspective view of a perovskite solar cell. [Diagram 3] FIG. 1 is an explanatory diagram of power generation in a perovskite solar cell. [Figure 4] FIG. 1 is an explanatory diagram showing a procedure for producing a perovskite solar cell. [Diagram 5] FIG. 1 shows a synthesis scheme of a hole transport material (P1) prepared in Example 1. [Figure 6] FIG. 2 shows the results of 1H NMR analysis confirming the synthesis of the hole transport material (P1) prepared in Example 1. [Figure 7] FIG. 2 shows the results of mass spectrometry confirming the synthesis of the hole transport material (P1) prepared in Example 1. [Figure 8] FIG. 2 shows the results of ultraviolet-visible-near infrared spectroscopic analysis confirming the synthesis of the hole transport material (P1) prepared in Example 1. [Figure 9] 1 is a graph showing the results of cell performance evaluation of the solar cells investigated in Example 3, showing the IV characteristics of each solar cell investigated. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0029] An embodiment of a perovskite solar cell 10 (one example of a solar cell 10; hereinafter, referred to as "solar cell 10") using a hole transport material according to the present invention will be described below with reference to the drawings. In this embodiment, as one example of a solar cell 10, a solar cell 10 configured with a perovskite layer 44 made of an organic and inorganic hybrid compound will be described. However, the present invention is not limited to the following embodiment, and various modifications are possible without departing from the spirit of the present invention.

[0030] (Basic configuration of solar cell 10 according to this embodiment) As shown in FIG. 1 and FIG. 2, the solar cell 10 according to the present embodiment includes a substrate 2 having a transparent substrate 21 and a transparent conductive film 22, a blocking layer 3 provided on the substrate 2, which transfers electrons to the transparent conductive film 22 and separates the hole transport layer 5 and the transparent conductive film 22 to prevent recombination of electrons and holes (reverse electron transfer), a power generation layer 4 provided on the blocking layer 3 and formed by laminating a perovskite layer 44 excited by light to generate electrons on a porous semiconductor 41, and a hole transport layer 5 provided on the power generation layer 4 through which holes generated in the perovskite layer 44 pass. The solar cell 10 also includes an electrode 6 provided on the surface of the blocking layer 3 and composed of a photoelectrode 61 that emits electrons through the transparent conductive film 22 and a counter electrode 62 that is provided on the surface of the hole transport layer 5 and receives electrons. The arrangement of the electrode 6 is not particularly limited as long as it is possible to transfer electrons, for example, by connecting the photoelectrode 61 to the transparent conductive film 22 with a conductor. In order to increase the durability of the solar cell 10, the counter electrode 62 may be protected by a transparent substrate 21 or the like.

[0031] The transparent substrate 21 is made of a material having optical transparency. For example, a transparent glass substrate, a frosted semi-transparent glass substrate, a transparent resin substrate, etc. can be used. For the transparent conductive film 22, for example, fluorine-doped tin oxide (FTO), tin oxide (TO), tin-doped indium oxide (ITO), zinc oxide (ZnO), aluminum-doped zinc oxide (AZO), etc. can be used.

[0032] The blocking layer 3 and the porous semiconductor 41 are preferably made of a metal oxide, such as titanium dioxide (TiO2), zinc oxide (ZnO), niobium oxide (Nb2O5), tin dioxide (SnO2), or aluminum oxide (Al2O3). In particular, it is preferable to configure the blocking layer 3 as a sintered body of titanium dioxide (TiO2), which can secure a large surface area for stacking the perovskite layer 44. In addition, the blocking layer 3 is formed so that a part of it extends into the transparent conductive film 22, and the transparent conductive film 22 is partitioned. Furthermore, the blocking layer 3 forms a dense insulating layer 31 so that electrons can pass through in the stacking direction but are difficult to move in the lateral direction. In other words, electrons that have entered from the blocking layer 3 move smoothly in the stacking direction of the transparent conductive film 22 and are supplied to the photoelectrode 61, and the insulating layer 31 prevents the electrons from moving to the counter electrode 62, so that no short circuit occurs.

[0033] The perovskite layer 44 is produced by reacting a compound (PbX2, X = halogen element) composed of lead and halogen element X with methylammonium iodide (CH3NH3I: hereinafter sometimes abbreviated as "MAI"). Specifically, a solution 42 containing lead and halogen element X is infiltrated into the inside of the pores of a porous semiconductor 41, dried, and then immersed in a mixed solution 43 of MAI, and crystals of a perovskite compound (CH3NH3PbI3 when X = I) that forms the perovskite layer 44 are rapidly produced. Note that although iodine, bromine, chlorine, etc. can be used as the halogen element X, it is preferable to use iodine, which has high morphological stability. In addition, a mixed cation-mixed halide ((FAPbI3)) using MABr and 0.2M lead bromide (PbBr2), FAI and lead iodide (PbI2) was also used. 1-x (MAPbBr3) x ) can also be used. For example, (FAPbI3) 0.85 (MAPbBr3) 0.15 etc. can be suitably used.

[0034] A hole transport material described later is used for the hole transport layer 5. For the electrode 6, for example, a simple metal or alloy of a metal such as gold, platinum, silver, or copper, or an oxide conductor such as fluorine-doped tin oxide (FTO) or tin-doped indium oxide (ITO) can be used.

[0035] Here, the principle of how the solar cell 10 generates electricity will be described with reference to Fig. 3. When light such as sunlight or indoor light is incident on the transparent substrate 21, this incident light is hardly absorbed and passes through the substrate 2 and the blocking layer 3, and most of it reaches the power generation layer 4. When the incident light that has reached the power generation layer 4 is irradiated onto the perovskite layer 44, the perovskite layer 44 absorbs the light energy and becomes excited. When the energy level of the perovskite layer 44 becomes higher than the conduction band potential of the metal oxide that is the porous semiconductor 41 by a predetermined level or more due to this excitation, electrons are injected from the perovskite layer 44 into the porous semiconductor 41. The injected electrons pass through the blocking layer 3 and are collected by the photoelectrode 61.

[0036] On the other hand, holes generated in the perovskite layer 44 reach the counter electrode 62 via the hole transport layer 5, where they recombine with electrons that have passed through the external load 7. In other words, a potential gradient is generated between the photoelectrode 61 and the counter electrode 62, so that power can be supplied by connecting the external load 7 between the two electrodes.

[0037] (Procedure for producing solar cell 10 according to this embodiment) The procedure for producing the solar cell 10 according to this embodiment will be described with reference to FIG. 4. However, the present invention is not limited to the following embodiment, and various modifications are possible without departing from the spirit of the invention. The solar cell 10 can be produced with reference to known techniques such as those described in Michael Saliba et al., “Correction to “How to Make over 20% Efficient Perovskite Solar Cells in Regular (nip) and Inverted (pin) Architectures”, Chem. Mater., 2018, 30, 4193-4218.

[0038] First, the transparent conductive film 22 is formed on the transparent substrate 21 to prepare the substrate 2. The transparent conductive film 22 is laminated on the transparent substrate 21 by, for example, CVD (chemical vapor deposition) or sputtering. Next, the transparent conductive film 22 is partially removed by laser scribing to form a recess 221 for the insulating layer 31, and then washed. Next, the blocking layer 3 is formed on the entire surface of the substrate 2 by ALD (atomic layer deposition) or SPD (spray pyrolysis). The blocking layer 3 is preferably formed as a TiO2 dense layer. Next, a porous semiconductor 41, which is a nanoparticle sintered layer, is formed near the center on the masked substrate 2 and blocking layer 3. It is preferably formed as a TiO2 porous layer (p-TiO2). This porous semiconductor 41 is formed by diluting a nanoparticle paste with a solvent, applying and drying, for example, by spin coating at a rotation speed of 4000 rpm to 6000 rpm, and then removing the mask and heating at 450°C to 550°C to form a sintered layer.

[0039] For example, a solution 42 of PbI2 in N,N-dimethylformamide is prepared and dropped onto the porous semiconductor 41, after which the solution is permeated into the pores (p-TiO2) and excess solution is removed by spin coating at a rotation speed of, for example, 5000 rpm to 8000 rpm. The solution is then dried at 60°C to 120°C (preferably 70°C to 90°C) to form a PbI2 layer.

[0040] The porous semiconductor 41, in which the substrate 2, blocking layer 3, and lead iodide have been infiltrated, is immersed in an isopropyl alcohol solution 43 (2-20 mg / ml) of MAI (CH3NH3I) at 0°C to 80°C (preferably at room temperature) (MAI immersion method). PbI2 and MAI react to form a perovskite compound [(CH3NH3)PbI3(MAPbI3)] as a perovskite layer 44 inside and on the top of the pores of the porous semiconductor 41, and then the porous semiconductor 41 is flooded with a pure isopropyl alcohol solution and dried at 60°C to 120°C (preferably 70°C to 100°C). The mixed cation-mixed halide ((FAPbI3) 1-x (MAPbBr3) x ) type perovskite compounds can be prepared in a similar manner.

[0041] The hole transport material according to the present embodiment is prepared as, for example, a chlorobenzene solution of 60 to 90 mg / ml. The solution is dropped onto the perovskite layer 44, and excess solution is removed by spin coating, followed by drying to form the hole transport layer 5. The hole transport material may contain an additive such as 4-isopropyl-4'-methyldiphenyliodonium tetrakis(pentafluorophenyl)borate (hereinafter, sometimes referred to as "TPFB"). When TPFB is added, the TPFB is preferably 0.01% by weight to 100% by weight of the hole transport material, and particularly preferably 0.1% by weight to 50% by weight. For example, the hole transport material according to the present embodiment is weighed out to be 30 mM, and TPFB equivalent to 10% by weight is added thereto, and the resulting solution is dissolved in chlorobenzene to form the hole transport layer 5.

[0042] The steps from forming the PbI2 layer to forming the hole transport layer 5 are preferably carried out in a dry nitrogen atmosphere such as in a glove box. Finally, a thin film of gold or the like is attached to the surfaces of the blocking layer 3 and the hole transport layer 5 by a method such as vacuum deposition to form an electrode 6.

[0043] In the above-mentioned manufacturing procedure, the crystal growth of the perovskite compound forming the perovskite layer 44 is controlled in two steps, but this may be performed in one step. For example, a perovskite ((CH3NH3)PbI3) solution is permeated into the pores of the porous semiconductor 41 by spin coating. Toluene is dropped during spinning to precipitate microcrystals and make the surface mirror-finished (poor solvent precipitation method). Then, the hole transport layer 5 may be formed from the hole transport material according to this embodiment.

[0044] (Hole Transport Material According to the Present Embodiment) The hole transport material according to this embodiment has a DAD structure, and a suitable example thereof is a compound represented by the following general formula (1):

[0045] [ka]

[0046] An electron-accepting group (electron-withdrawing group) is introduced into the A portion, which is configured as a linear 2,5-oligomer of unsubstituted or substituted thiophene. Furthermore, the D portions are linked to both ends of the A portion, and each D portion is preferably configured as the same group.

[0047] The D portion is constituted as an electron-donating group, and preferably has one structure selected from the following group (I), group (II), group (III), group (IV), or group (V). The wavy line in the group indicates the bonding position with the A portion.

[0048] [ka]

[0049] [ka]

[0050] [ka]

[0051] [ka]

[0052] [ka]

[0053] In the groups (I), (II), (III), (IV), and (V), X and Y are each independently an integer of 0, 1, or 2. Accordingly, the groups (I) and (II) each include a diphenylamino group (X=0, Y=0), a 4-(diphenylamino)phenyl group (X=1, Y=0), a 4'-(diphenylamino)[1,1'-biphenyl]-4-yl group (X=2, Y=0), a 5-(diphenylamino)thiophen-2-yl group (X=0, Y=1), a 5'-(diphenylamino)[2,2'-bithiophene]-5-yl group (X=0, Y=2), a 5-[4-(diphenylamino)phenyl group (X=0, Y=0 ... and 5-[4'-(diphenylamino)[1,1'-biphenyl]-4-yl]thiophen-2-yl group (X=1, Y=1), 5-[4'-(diphenylamino)phenyl][2,2'-bithiophene]-5-yl group (X=1, Y=2), and 5'-[4'-(diphenylamino)[1,1'-biphenyl]-4-yl][2,2'-bithiophene]-5-yl group (X=2, Y=2).

[0054] In groups (I) and (II), each substituent is independently selected; R 1 -H, -C n H 2n+1 , -OC n H 2n+1 , and -SC n H 2n+1 where n=an integer from 1 to 8; R 3 -H, -C n H 2n+1 , -OC n H 2n+1 , and -SC n H 2n+1 where n is an integer from 1 to 8; and R 1 and R 3 may be the same or different, but cannot be simultaneously -H. Therefore, R 1 and R 3 teeth 、 At least one of them is -C n H 2n+1 , -OCn H 2n+1 , and -SC n H 2n+1 is selected from.

[0055] R 1 and R 3 -C in n H 2n+1 is an alkyl group, whether linear or branched. There is no particular restriction on the chain length as long as n is within the range of 1 to 8. Specifically, the alkyl group may be a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, an s-butyl group, an t-butyl group, an n-pentyl group, an isopentyl group, an neopentyl group, an t-pentyl group, an s-pentyl group, a 2-methylbutyl group, a 1-ethylpropyl group, a 2-ethylpropyl group, an n-hexyl group, an isohexyl group, an neohexyl group, an t-hexyl group, a 2,2-dimethylbutyl group, a 2-methylpentyl group, a 3-methylpentyl group, a 1-ethylbutyl group, a 2-ethylbutyl group, a 1-propylpropyl group, an n-heptyl group, an isoheptyl group, an s-heptyl group, an t-heptyl group, a 2,2-dimethylpentyl group, a 3,3-dimethylpentyl group, a 1-methylhexyl group, a 2 Examples of the alkyl groups include 1-methylhexyl group, 3-methylhexyl group, 4-methylhexyl group, 1-ethylpentyl group, 2-ethylpentyl group, 3-ethylpentyl group, 1-propylbutyl group, 2-propylbutyl group, n-octyl group, isooctyl group, t-octyl group, neooctyl group, 2,2-dimethylhexyl group, 3,3-dimethylhexyl group, 4,4-dimethylhexyl group, 1-methylheptyl group, 2-methylheptyl group, 3-methylheptyl group, 4-methylheptyl group, 5-methylheptyl group, 1-ethylhexyl group, 2-ethylhexyl group, 3-ethylhexyl group, 4-ethylhexyl group, 1-propylpentyl group, 2-propylpentyl group, and 3-propylpentyl group.

[0056] In group (I), R 2a1 , R 2a2 , R 2b1 , and R 2b2 are each independently selected from -H, -F, and -CF; R 2a1 , R 2a2, R 2b1 , and R 2b2 may be the same or different, but R 2a1 and R 2a2 At least one of them is -H and R 2b1 and R 2b2 At least one of the groups is -H. Therefore, R 2a1 , R 2a2 , R 2b1 , and R 2b2 When -F or -CF3 is introduced, R 2a1 and R 2a2 Either one of and / or R 2b1 and R 2b2 It is introduced into either one of the above.

[0057] In group (II), R 2a1 and R 2a2 are each independently selected from -H, -F, and -CF; R 2a1 and R 2a2 may be the same or different, but R 2a1 and R 2a2 At least one of the groups is -H. Therefore, R 2a1 and R 2a2 When -F or -CF3 is introduced, R 2a1 and R 2a2 It is introduced into one of the following.

[0058] In formula (II), R 4 -H, -C n H 2n+1 , -OC n H 2n+1 , and -SC n H 2n+1 where n is an integer from 1 to 8. 4 -C in n H 2n+1 , and -OC n H 2n+1 , and -SC n H 2n+1 -C n H 2n+1is an alkyl group, the definition of which is as explained above.

[0059] In group (II), when Y is 1 or 2 and a thiophene ring is present, R 5 is introduced at the 3- or 4-position of the thiophene ring. 5 -H and -C n H 2n+1 where n is an integer from 1 to 8. 5 -C in n H 2n+1 is an alkyl group, the definition of which is as explained above.

[0060] In groups (III), (IV) and (V), R D is preferably selected from the following groups (I'):

[0061] [ka]

[0062] Two R in groups (III), (IV), and (V) D The groups (I') may be different or the same, but are preferably constituted as the same group.

[0063] In group (I'), each substituent is independently selected; R 1 ´ is -H, -C n H 2n+1 , -OC n H 2n+1 , and -SC n H 2n+1 where n=an integer from 1 to 8; R 3 ´ is -H, -C n H 2n+1 , -OC n H 2n+1 , and -SC n H 2n+1 where n is an integer from 1 to 8; and R 1 ´ and R 3' may be the same or different, but cannot be -H at the same time. 1 ´ and R 3 teeth 、 At least one of them is -C n H 2n+1 , -OC n H 2n+1 , and -SC n H 2n+1 is selected from.

[0064] R 1 ´ and R 3 -C in ´ n H 2n+1 is an alkyl group, which may be linear or branched. There is no particular restriction on the chain length as long as it is within the range of n=1 to 8. The definition of the alkyl group is as explained above.

[0065] In the group (I'), R 2a1 ´, R 2a2 ´, R 2b1 ´, and R 2b2 R ' is independently selected from -H, -F, and -CF; 2a1 ´, R 2a2 ´, R 2b1 ´, and R 2b2 ' may be the same or different, but R 2a1 ´ and R 2a2 ´ is at least one of -H and R 2b1 ´ and R 2b2 ´ has at least one -H. Therefore, R 2a1 ´, R 2a2 ´, R 2b1 ´, and R 2b2 When -F or -CF3 is introduced as R 2a1 ´ and R 2a2 ´ and / or R 2b1 ´ and R 2b2 ´ is introduced into either

[0066] The D portion may preferably be a tetrakis-4-alkoxyphenylcarbazole group, and more preferably a tetrakis-4-methoxyphenylcarbazole group. Preferably, it is a 4-(bis(4-alkoxyphenyl)amino)phenyl group, and more preferably a 4-(bis(4-methoxyphenyl)amino)phenyl group. Also, it may preferably be a bis(4-alkoxyphenyl)amino group, and more preferably a bis(4-methoxyphenyl)amino group. Although not limited to these, those having a tertiary amine group substituted with such a phenyl group are particularly preferred. In addition, the alkoxy group contained in the above group is preferably selected from an ethoxy group, a propoxy group, a butoxy group, and the like, in addition to a methoxy group.

[0067] The A part has a linear thiophene oligomer structure in which unsubstituted or substituted thiophenes are linked at the 2-position (5-position), and is constituted as a poly(thiophene-2,5-diyl) group. When such a poly(thiophene-2,5-diyl) group has a substituent, it can be introduced at the 3-position or 4-position, or both, of each thiophene unit. The substituent is a linear or branched alkyl group having 1 to 12 carbon atoms. Both ends of the poly(thiophene-2,5-diyl) group are bonded to the D part at the 5-position (2-position), respectively.

[0068] Specifically, the A portion has a structure represented by the following group (VI): The wavy line in the group indicates the bonding position with the D portion. [ka]

[0069] In the group (VI), Z is not particularly limited as long as it is a repeating unit of an integer of 2 or more, but is preferably 2 to 11, more preferably 2 to 7. From the viewpoint of maintaining the planar structure of the molecule and facilitating intermolecular stacking, Z is particularly preferably an odd number such as 3, 5, or 7, for example, 3 or 5.

[0070] R in group (VI) A1and R A2 are each independently -H or -C m H 2m+1 is a -C m H 2m+1 The R group is an alkyl group. A1 and R A2 Ga-C m H 2m+1 When the group is -C m H 2m+1 The group may be straight-chain or branched. m H 2m+1 The chain length of the group is not particularly limited as long as m is an integer in the range of 1 to 12. It is preferably in the range of 1 to 8, and more preferably 4 to 6. m H 2m+1 The group is an alkyl group, and the definition of the alkyl group is as explained above. In addition to the specific examples of the alkyl group mentioned above, examples thereof include a linear or branched nonyl group, a decyl group, an undecyl group, and a dodecyl group. An n-hexyl group is particularly preferred. A1 and R A2 does not contain any heteroatom.

[0071] In addition, R in group (VI) A1 and R A2 are each independently -H or -C m H 2m+1 Since it is a -C group, m H 2m+1 The group R of each thiophene unit in group (VI) A1 and R A2 In addition, the case where some or all of the thiophene units in the group (VI) are unsubstituted is also included.

[0072] Here, in group (VI), for each of Z repeating units in (), R A1 and R A2 may be the same or different. Thus, the group (VI) is a unit of all R A1 Ni-C m H 2m+1Similarly, all R of each thiophene unit may be configured as a thiophene oligomer structure having an R A2 Ni-C m H 2m+1 The thiophene oligomer structure may be formed by introducing a -C group (so-called head-to-tail type thiophene oligomer structure). m H 2m+1 The groups may all be the same, or some or all may be different. A1 Ni-C m H 2m+1 Thiophene units with R groups A2 Ni-C m H 2m+1 The thiophene oligomer structure may be configured to include both thiophene units having a group introduced therein, or a thiophene oligomer structure in which some or all of the thiophene units are unsubstituted.

[0073] The A part is preferably exemplified by those having the following structure, and the hexyl group may be introduced at either the 3rd or 4th position of each thiophene unit. Therefore, hexyl groups may be introduced at all 3rd positions and all 4th positions of each thiophene unit constituting the following linear thiophene oligomer, or some hexyl groups may be introduced at the 3rd position of the thiophene unit and the rest may be introduced at the 4th position of the thiophene unit. Furthermore, hexyl groups may be introduced at all 3rd and 4th positions of each thiophene unit. In the following structure, the wavy line indicates the bonding position with the D part. [ka]

[0074] [Preferable Examples of Hole Transport Material According to the Present Embodiment] A suitable example of the hole transport material according to this embodiment is a compound represented by the following general formula (2), and a particularly preferred example is a compound represented by the following general formula (3). Hereinafter, the hole transport material represented by general formula (3) may be referred to as "P1".

[0075] [ka] [ka]

[0076] The structure of the compound of general formula (2), which is a suitable example of the hole transport material according to this embodiment, will be described in detail. The compound of general formula (2) has a DAD type structure. The A part is configured as a tri(hexylthiophene-2,5-diyl) group, and a tetrakis-4-methoxyphenylcarbazole group is introduced as the D part at each end of the A part. The tri(hexylthiophene-2,5-diyl) group of the A part can be configured as a tri(3-hexylthiophene-2,5-diyl) group as in P1 of general formula (3), for example, but there is no particular restriction on the position of the hexyl group. Therefore, a structure in which a hexyl group is introduced at the 3rd position of the thiophene unit and a hexyl group is introduced at the 4th position may be combined.

[0077] [Method of synthesizing hole transport material according to this embodiment] The hole transport material according to the present embodiment can be easily synthesized by referring to the synthesis method described in the following Example 1. Note that Example 1 shows an example of a synthesis method for P1, which is a suitable example of the hole transport material according to the present embodiment, but the synthesis is not limited thereto, and other suitable methods can be used for synthesis.

[0078] A suitable example of the hole transport material according to this embodiment has a DAD type structure, and the A part is configured as a linear 2,5-oligomer structure of thiophene, and has a structure in which the D part is introduced at each end. In the synthesis, first, a linear 2,5-oligomer of thiophene constituting the A part is synthesized. For example, it can be synthesized by subjecting a halogenated thiophene in which the 2-position and the 5-position are substituted with halogen atoms such as Br and an alkyl substituent is introduced as necessary, and a thiophene-tetramethyl-dioxaborolane in which the 2-position is boronized and an alkyl substituent is introduced as necessary to a Suzuki-Miyaura coupling reaction. The number of thiophene units contained in the thiophene oligomer can be controlled by appropriately changing the substitution position of the halogen atom of thiophene, the amount of the reacting reagent, the reaction conditions, etc. It is noted that the synthesis of a thiophene oligomer consisting of an odd number of thiophene units can be performed more easily, and for example, it can be synthesized by linking thiophene to both ends of the above-mentioned halogenated thiophene. Next, Br is introduced into the D moiety of the synthesized thiophene oligomer by bromination reaction using NBS or the like. The hole transport material according to this embodiment can be synthesized by introducing the D moiety into the Br derivative of this thiophene oligomer by cross-coupling or the like known in the art. The above-mentioned preferred example P1 has a tetrakis-4-methoxyphenylcarbazole group introduced as the D moiety, and can be synthesized, for example, by Buchwald-Hartwig coupling between a Br derivative of a linear 2,5-oligomer of thiophene and N3,N3,N6,N6-tetrakis(4-methoxyphenyl)-9H-carbazole-3,6-diamine (5). EXAMPLES

[0079] The present invention will now be described in detail with reference to the following examples.

[0080] Example 1 Preparation of hole transport material (P1) The hole transport material prepared in this example is called "P1" and is represented by the following general formula (3), and is a compound in which the A part is constituted by a tri(3-hexylthiophene-2,5-diyl) group and tetrakis-4-methoxyphenylcarbazole groups are introduced as D parts on both ends of the A part. The synthesis scheme is explained based on Figure 5.

[0081] In the synthesis of P1, first, 2,5-dibromo-3-hexylthiophene (1) and 2-hexyl-thiophene-tetramethyl-dioxaborolane (2) were subjected to Suzuki-Miyaura coupling reaction to synthesize the 2'2':5',2''-terthiophene derivative (3) constituting the A part (hexyl group introduced at the 3-position of each thiophene unit). Next, bromination reaction with NBS was performed to synthesize 5,5''-dibromo-2'2':5',2''-terthiophene derivative (4) by introducing bromo groups to 5 and 5'' of compound (3). Then, compound (4) was subjected to Buchwald-Hartwig coupling with N3,N3,N6,N6-tetrakis(4-methoxyphenyl)-9H-carbazole-3,6-diamine (5) to synthesize P1, which was then purified by a standard method. The details of the synthesis and purification of P1 are explained below.

[0082] (synthesis) [Step 1] Synthesis of compound (3) (2´2´:5´,2´´-terthiophene derivative) 2,5-dibromo-3-hexylthiophene (1) (0.5 g, 1.533 mmol) and 2-hexyl-thiophene-tetramethyl-dioxaborolane (2) (1.13 g, 3.833 mmol) were added to a 50 mL round-bottom flask. Anhydrous toluene (20 mL) and 2 M potassium carbonate (K2CO3) (15 mL) were added. Pd(PPh3)4 (0.22 g, 0.2 mmol) was then added, and the mixture was refluxed for 24 hours. After the reaction was completed, the mixture was cooled to room temperature and the reaction mixture was dissolved in 30 mL of dichloromethane (hereinafter sometimes referred to as "DCM"). The reaction mixture was then extracted with deionized water (20 mL). The organic layer was extracted three times with DCM, dried over anhydrous magnesium sulfate, and the solvent was removed by evaporation. The crude product was then separated by column chromatography on silica gel using hexane as an eluent to obtain pure compound (3) as a colorless liquid compound (yield: 0.7 g, yield: 91.14%).

[0083] [Step 2] Synthesis of compound (4) (5,5´´-dibromo-2´2´:5´,2´´-terthiophene derivative) Compound (3) (0.68 g, 1.36 mmol) obtained in step 1 was dissolved in N,N-dimethylformamide (hereinafter, sometimes referred to as "DMF") (10 mL) and cooled to 0°C. Then, N-bromosuccinimide (hereinafter, sometimes referred to as "NBS") (0.5 g, 2.72 mmol) was added in portions over 4 hours. The reaction mixture was stirred at room temperature overnight, and then water (10 mL) and DCM (10 mL) were added successively. The aqueous phase was extracted with DCM (3 x 20 mL). The organic layers were combined, dried over anhydrous Na2SO4, and the solvent was removed in vacuum. The obtained crude product was purified by silica gel chromatography using hexane as an eluent to obtain pure compound (4) as a colorless liquid compound (yield: 0.7 g, yield: 78.3%).

[0084] [Step 3] Synthesis of P1 Compound (4) (0.20 g, 0.30 mmol) obtained in step 2, N3,N3,N6,N6-tetrakis(4-methoxyphenyl)-9H-carbazole-3,6-diamine (5) (0.4 g, 0.64 mmol), Pd2(dba)3 (0.05 g, 0.06 mmol), tritert-butyl phosphine tetrafluoroborate (0.04 g, 0.12 mmol) and potassium tert-butoxide (0.12 g, 1.82 mmol) were mixed in anhydrous toluene (10 mL). The reaction mixture was heated at 110° C. for 24 hours. After the reaction, the mixture was cooled to room temperature and extracted with DCM and washed with brine solution. Then, the mixture was dried over anhydrous Na2SO4 and the solvent was evaporated to obtain the crude product of P1.

[0085] (Refining and Confirmation) The crude product obtained in step 3 was purified twice by silica gel column chromatography using ethyl acetate:hexane=2:8 as an eluent to obtain pure P1 as a pale green solid compound. This material was further purified by recrystallization from DCM / methanol to obtain P1 as a pale green solid (yield: 0.08 g, yield: 15%, HPLC purity: 88%). 1 The synthesis and purification of P1 were confirmed by H NMR analysis, mass spectrometry (hereinafter sometimes referred to as "Mass"), high performance liquid chromatography analysis (hereinafter sometimes referred to as "HPLC"), and ultraviolet-visible near-infrared spectroscopy analysis (hereinafter sometimes referred to as "UV-Vis"). 1 The results of the 1 H NMR analysis are shown in FIG. 7, the results of the mass analysis are shown in FIG. 8, and the results of the ultraviolet-visible-near infrared spectroscopic analysis are shown in FIG.

[0086] (Comparative Example 1) Preparation of DHCF-3 The hole transport material prepared as Comparative Example 3 is called "DHCF-3" represented by the following general formula (E), and is a compound described in Patent Document 1 (JP Patent Publication No. 2023-46046) described in the above [Background Art] section. In detail, DHCF-3 is a compound in which a 4-(bis(4-methoxyphenyl)amino)phenyl group is introduced as a D portion at each of the 2-position and 7-position on the fluorene ring constituting the A portion, and a 4-(bis(4-methoxyphenyl)amino)phenyl group, which is the same group as the D portion, is introduced at the 9-position on the fluorene ring constituting the A portion via a carbon-carbon double bond. Synthesis and purification can be performed based on the description in Patent Document 1, but will be briefly described below.

[0087] (synthesis) 2,7-Di(4-(bis(4-methoxyphenyl)amino)phenyl)-9H-fluorene (1) (0.01 g, 0.13 mmol), 4-(bis(4-methoxyphenyl)amino)benzaldehyde (2) (0.056 g, 0.17 mmol), TBAB (0.015 g, 0.45 mmol) and dry toluene (8 mL) were added to a 25 mL round bottom flask. Then, 40% sodium hydroxide (NaOH) (6 mL) was added. The reaction mixture was heated to reflux under argon atmosphere for 8 hours. After cooling, the reaction mixture was poured into water and extracted with DCM. It was then washed with brine solution and concentrated in vacuum to give the crude product.

[0088] (purification) The obtained crude product was purified by column chromatography (silica gel: 100-200 mesh) using petroleum ether:DCM=5:95 as an eluent 2-3 times to obtain a yellow solid DHCF-3 (yield: 0.10 g, 71.02%).

[0089] The structures of the hole transport materials synthesized in Example 1 and Comparative Example 1 are summarized below. [ka]

[0090] Example 2: Fabrication of solar cell 10 Hereinafter, a fabrication example of the solar cell 10 will be described as Example 2. The solar cell 10 can be fabricated with reference to known techniques such as those described in Chem. Mater., 2018, 30, 4193-4218, etc.

[0091] As an example, fluorine-doped tin oxide (FTO) glass (23 mm x 14 mm x 1.6 mm) was used for the transparent substrate 21. This FTO glass was laser scribed to form a recess 221 by removing the FTO, and was thoroughly washed. Next, a TiO2 dense film was formed as the blocking layer 3 by spray pyrolysis (SPD). Furthermore, a solution of commercially available TiO2 nanoparticle paste diluted with ethanol was dropped, applied by spin coating, and dried at 100°C. After drying, the substrate was baked at 450°C to form a TiO2 nanoparticle layer that would become the porous semiconductor 41. After baking, the substrate was cooled to room temperature.

[0092] Next, a perovskite precursor solution for forming the perovskite layer 44 was prepared. First, FAI (CH(NH2)2I) was weighed out, and a 1.7M PbI2 / dimethylformamide (DMF) + dimethyl sulfoxide (DMSO) solution prepared in advance was poured into it to prepare a FAPbI3 solution. Next, MAI (CH3NH3I) was weighed out, and a 1.7M PbBr2 / dimethylformamide (DMF) + dimethyl sulfoxide (DMSO) solution prepared in advance was poured into it to prepare a MAPbBr3 solution.

[0093] Finally, the FAPbI3 solution, the MAPbBr3 solution, and a previously prepared 1.7 M CsI / dimethyl sulfoxide (DMSO) solution were mixed to prepare a precursor solution to be subjected to spin coating.

[0094] The perovskite layer 44 was formed by dropping the above-mentioned precursor solution onto the TiO2 porous film and applying it by spin coating. After the application was completed, the film was heated at 100°C for 60 minutes and then cooled to room temperature.

[0095] Next, the hole transport layer 5 was prepared. As the hole transport material, P1 synthesized in the above Example 1 and DHCF-3 synthesized in the above Comparative Example 1 were used. Each hole transport material solution was weighed out so as to have a final concentration of 30 mM, and TPFB equivalent to 10% by weight was weighed out and added to the hole transport material. A mixture of the hole transport material and TPFB was dissolved in chlorobenzene to prepare a hole transport material solution. Note that cobalt complex (FK209), which is commonly used as a dopant, was not added. The hole transport layer 5 was formed by dropping the hole transport material solution onto the perovskite film and forming it by a spin coating method.

[0096] After the hole transport layer 5 was formed, a gold film of about 100 nm was formed by vacuum deposition, which was then removed to form the electrode 6, which was then laminated.

[0097] Example 3: Evaluation of cell performance of solar cell 10 In this example, an evaluation was performed on the cell performance of the solar cell 10. Here, the solar cell 10 using P1 synthesized in the above Example 1 and DHCF-3 synthesized in the above Comparative Example 1 as hole transport materials was investigated.

[0098] The hole transport materials P1 (general formula (3)) of Example 1 and DHCF-3 (general formula (E)) of Comparative Example 1 examined in this example both have a DAD structure. The two materials have a significantly different structure in the A portion, with P1 of Example 1 comprising a tri(3-hexylthiophene-2,5-diyl) group in the A portion and DHCF-3 of Comparative Example 1 comprising a fluorene ring in which a 4-(bis(4-methoxyphenyl)amino)phenyl group is introduced at the 9-position on the fluorene ring of the A portion via a carbon-carbon double bond. In both D parts, a tertiary amine group substituted with a phenyl group was introduced. P1 in Example 1 was constructed by introducing tetrakis-4-methoxyphenylcarbazole groups to both ends of the tri(3-hexylthiophene-2,5-diyl) group in the A part, and DHCF-3 in Comparative Example 1 was constructed by introducing 4-(bis(4-methoxyphenyl)amino)phenyl groups, which are the same as the substituents in the A part, into the 2- and 7-positions on the fluorene ring in the A part.

[0099] Table 1 and Figure 9 show the results of the cell performance evaluation of solar cell 10. Table 1 summarizes the parameters of the short circuit current density (hereinafter sometimes referred to as "Jsc"), open circuit voltage (hereinafter sometimes referred to as "Voc"), fill factor (hereinafter sometimes referred to as "FF"), and conversion efficiency of solar cell 10. FF is the maximum output P at the point where the product of the current and voltage is maximum. max The conversion efficiency (PCE (%)) was calculated by dividing by (Voc × Jsc × FF ÷ incident light intensity).

[0100] [Table 1]

[0101] From the results in Table 1, the conversion efficiency of P1 in Example 1 was 20.1%, which was 20% or more, and showed higher solar cell characteristics than DHCF-3 in Comparative Example 1. It was found that the cell performance changed due to the difference in the structure of the A part. In P1, the linear thiophene oligomer structure introduced as the A part has a planar structure, and it is considered that the push-pull effect in the molecule increases and the charge transfer characteristics are improved by smoothly π-conjugating with the D part introduced at both ends. Furthermore, since the entire molecule of P1 has a planar structure, each component part in the molecule is arranged in a roughly plate-like shape. Therefore, it is considered that the P1 molecules are smoothly stacked with each other, and the hole transport performance in the hole transport layer 5 is improved. It is considered that the solar cell characteristics are improved as a result of these good characteristics of P1.

[0102] Furthermore, it is expected that P1 of Example 1 will smoothly move holes within and between molecules, and thus will suppress oxidation of the molecules and increase durability. Furthermore, since an alkyl group is introduced into the linear thiophene oligomer structure constituting the A portion of P1, P1 has good solubility in a solvent, and after dissolving P1 in a suitable solvent, the hole transport layer 5 can be formed by a wet process such as a coating method by spin coating, which is advantageous in that the solar cell 10 can be easily fabricated.

[0103] It was also found that the addition of TPFB makes it possible to construct a highly durable solar cell 10. The addition of TPFB has the advantage that it can be carried out by a simple process of simply dissolving it in a solvent together with a hole transport material.

[0104] Example 4: Synthesis of various hole transport materials A hole transport material was synthesized by modifying the group constituting the D portion of P1. The structure of the synthesized compound is shown below. [ka]

[0105] These compounds are expected to have similar properties to P1.

[0106] In the above-described embodiment, the following configurations are envisaged. (1) A hole transport material having a donor-acceptor-donor (DAD) structure represented by the following general formula (1): [ka] [In general formula (1), The two D regions are regions having the same structure, Each D moiety has a structure selected from the following groups (I), (II), (III), (IV), and (V): [ka] (In group (I), X and Y are each independently an integer of 0, 1, or 2. R 1 -H, -C n H 2n+1 , -OC n H 2n+1 , and -SC n H 2n+1 where n=an integer from 1 to 8; R 3-H, -C n H 2n+1 , -OC n H 2n+1 , and -SC n H 2n+1 where n=an integer from 1 to 8; However, R 1 and R 3 cannot be -H at the same time, R 2a1 , R 2a2 , R 2b1 , and R 2b2 are each independently selected from -H, -F, and -CF3, where R 2a1 and R 2a2 At least one of them is -H and R 2b1 and R 2b2 At least one of them is -H.) [ka] (In group (II), X and Y are each independently an integer of 0, 1, or 2. R 1 -H, -C n H 2n+1 , -OC n H 2n+1 , and -SC n H 2n+1 where n=an integer from 1 to 8; R 3 -H, -C n H 2n+1 , -OC n H 2n+1 , and -SC n H 2n+1 where n=an integer from 1 to 8; However, R 1 and R 3 cannot be -H at the same time, R 2a1 and R 2a2 are each independently selected from -H, -F, and -CF3, where R 2a1 and R 2a2 At least one of them is -H, R 4 -H, -C n H 2n+1 , -OC n H 2n+1 , and -SC n H 2n+1 where n is an integer from 1 to 8; Y is 1 or 2, and R 5 If exists, R 5 is introduced at the 3- or 4-position of the thiophene ring in group (II), -H and -C n H 2n+1 where n is an integer from 1 to 8. [ka] [ka] [ka] (In group (III), group (IV), and group (V), X and Y are each independently an integer of 0, 1, or 2; The Two R's D each independently has a structure represented by the following group (I'), [ka] (In the group (I´), X' and Y' are each independently an integer of 0, 1, or 2. R 1 ´ is -H, -C n H 2n+1 , -OC n H 2n+1 , and -SC n H 2n+1 where n=an integer from 1 to 8; R 3 ´ is -H, -C n H 2n+1 , -OC n H 2n+1 , and -SC n H2n+1 where n=an integer from 1 to 8; However, R 1 ´ and R 3 ´ is not simultaneously -H, R 2a1 ´, R 2a2 ´, R 2b1 ´, and R 2b2 are each independently selected from -H, -F, and -CF3, where R 2a1 ´ and R 2a2 ´ is at least one of -H and R 2b1 ´ and R 2b2 ´ At least one of them is -H. )) In general formula (1), Z is a repeating unit which is an integer from 2 to 11; R A1 and R A2 are each independently -H or -C m H 2m+1 group, where m=an integer from 1 to 12; For each Z repeating units in (), A1 and R A2 may be the same or different.

[0107] According to the above-mentioned configuration, it is possible to provide a hole transport material having excellent hole transport properties capable of stably and efficiently capturing and transporting holes. In detail, the hole transport material of this configuration has a DAD type structure, and the A part is configured as a linear thiophene oligomer structure, and the D part containing an electron donating group such as a tetrakis-4-methoxyphenylcarbazole group is introduced at both ends of the A part. By configuring in this way, the thiophene oligomer structure introduced as the A part has a planar structure, and smoothly π-conjugates with the D part introduced at both ends, so that the push-pull effect in the molecule is increased and the charge transfer property is improved. As a result, the transfer of electrons in the molecule is smooth and the charge separation of HOMO-LUMO is more clear. That is, in the hole transport material of this configuration, electrons are concentrated in the D part at the HOMO and HOMO-1 levels, and electrons are concentrated in the A part at the LUMO level. In this way, the hole transport material of this configuration can exhibit excellent hole transport properties due to the improved charge transfer property in the molecule. Furthermore, in the hole transport material of this configuration, the entire molecule has a planar structure, so that each component part in the molecule is arranged in a roughly plate-like shape. Therefore, the molecules are smoothly stacked with each other, and the transfer of holes between the molecules is smooth. When the hole transport material of this configuration is used as a hole transport layer 5, it is considered that the hole transport performance in the hole transport layer 5 is improved. Therefore, according to this configuration, conventional technical problems such as a decrease in hole transport performance due to a decrease in π conjugation caused by steric interference between the substituent of the A portion and the D portion are resolved, and a hole transport material exhibiting excellent hole transport properties can be provided.

[0108] In addition, since the hole transport material of the present configuration has a deep HOMO energy level, the arrangement with the HOMO level of the perovskite can be appropriately adjusted, which has the advantage that the hole transport properties can be improved and the solar cell efficiency can be easily improved.

[0109] The hole transport material of this configuration hardly absorbs light in the visible light range, and its light absorption intensity in the range of up to 450 nm is weaker than that of the conventionally widely used spiro-OMeTAD. Therefore, a solar cell 10 using the hole transport material of this configuration can minimize light absorption loss due to the hole transport material, and is expected to have high photoelectric conversion efficiency.

[0110] The hole transport material of this configuration also has excellent properties in terms of solubility in a solvent. In particular, by introducing an alkyl group into the thiophene oligomer structure constituting the A portion, it is expected that the solubility will be particularly improved. Therefore, wet processes such as a coating method by spin coating can also be used, and the hole transport layer 5 of the solar cell 10 can be easily formed. In addition, since the hole transport material according to this embodiment is soluble in a non-polar solvent, it is possible to prepare the hole transport layer 5 of the solar cell 10 using a solvent that is inexpensive and has a low environmental impact. On the other hand, when preparing the hole transport layer 5, the conventional spiro-OMeTAD generally uses chlorobenzene as a solvent. However, since chlorobenzene contains chlorine atoms in the molecule and is expensive, the cost of equipment including post-processing such as solvent disposal is high, and there are problems such as a large load on safety and the environment due to exhaust gas leakage.

[0111] In addition, the hole transport material according to the present embodiment can be synthesized in a short time with few synthesis steps using inexpensive raw materials, and a high purity product can be provided through a simple purification step. Therefore, it is possible to reduce the costs required for synthesis and purification without requiring expensive reagents or complicated steps, and it is possible to provide an inexpensive, high-performance hole transport material.

[0112] Furthermore, the hole transport material according to this embodiment allows smooth intra- and intermolecular hole movement, suppressing oxidation of the molecule and improving durability. In particular, by introducing an alkyl group into the thiophene oligomer structure constituting the A portion, the hydrophobic effect of the alkyl group can be used to further improve the water resistance of the solar cell 10 incorporating the hole transport material according to this embodiment. This is expected to improve the durability of the solar cell 10.

[0113] As described above, the hole transport material according to this embodiment has excellent properties and can be suitably used as a hole transport material for the solar cell 10.

[0114] (2) In the hole transport material of (1), all R in the Z repeating units in () A1 -C m H 2m+1 group, and all R A2 is -H, or all R in the Z repeating units in () A1 is -H, and all R in the Z repeating units in () A2 -C m H 2m+1 It is preferable that the group is a aryl group.

[0115] In the hole transport material according to this embodiment, by introducing an alkyl group into a certain position of the linear thiophene oligomer structure constituting the A portion, the electron-withdrawing property of the A portion is further improved, and the π-conjugation between DAD in the molecule becomes smoother, so that the push-pull effect in the molecule can be appropriately controlled, and the charge transfer property can be further improved. In addition, the hole transport performance is further improved by appropriate stacking of the hole transport materials. This makes it possible to provide a hole transport material having excellent hole transport properties, in particular, capable of stably and efficiently capturing and transferring holes. In addition, since the hole mobility in and between molecules is improved, the oxidation of the molecule is further suppressed, and further improvement in durability is expected.

[0116] (3) In the hole transport material of (1), RA1 and R A2 Ga-C m H 2m+1 When selecting a group, -C m H 2m+1 It is preferred that the group is an n-hexyl group.

[0117] In the hole transport material according to the present embodiment, by introducing a hexyl group into the linear thiophene oligomer structure constituting the A portion, the electron-withdrawing property of the A portion is further improved, and the π-conjugation between DAD in the molecule becomes smoother, so that the push-pull effect in the molecule can be appropriately controlled, and the charge transfer property can be further improved. In addition, the hole transport performance is further improved by appropriate stacking of the hole transport materials. This makes it possible to provide a hole transport material having excellent hole transport properties, particularly capable of stably and efficiently capturing and transferring holes. In addition, since the hole mobility in and between molecules is improved, the oxidation of the molecule is further suppressed, and the durability is further improved. By introducing a hexyl group having an appropriate chain length, the solubility of the hole transport material according to the present embodiment in a solvent is improved, which makes it easier to form the hole transport layer 5 of the solar cell 10 using the hole transport material, and the hydrophobic effect of the hexyl group is expected to further improve the durability of the solar cell 10.

[0118] In the hole transport material of (4)(1), Z is preferably 3 or 5.

[0119] In the hole transport material according to the present embodiment, the number of thiophene units in the linear thiophene oligomer constituting the A portion is 3 or 5, which improves the maintenance of the planar structure of the molecule and the ease of stacking between molecules. As a result, the π conjugation between DAD in the molecule becomes smoother, the push-pull effect in the molecule can be appropriately controlled, and the charge transfer characteristics can be further improved. In addition, the hole transport performance is further improved by appropriate stacking between hole transport materials. As a result, it is possible to provide a hole transport material having excellent hole transport characteristics that can capture and transfer holes stably and efficiently. In addition, since the hole mobility in and between molecules is improved, the oxidation of the molecule is further suppressed, and the durability is further improved. In addition, when synthesizing a thiophene oligomer structure, the synthesis of a thiophene oligomer structure composed of an odd number of thiophene units is easier, and the cost required for synthesis and purification can be further reduced.

[0120] In the hole transport material of (5)(1), it is preferred that the D portion is tetrakis-4-methoxyphenylcarbazole.

[0121] In the hole transport material according to the present embodiment, by configuring the D portion as tetrakis-4-methoxyphenylcarbazole having a planar structure, the π conjugation between DAD in the molecule becomes smoother, the push-pull effect in the molecule can be appropriately controlled, and the charge transfer characteristics can be further improved. In addition, the hole transport performance is further improved by appropriate stacking of the hole transport materials. This makes it possible to provide a hole transport material having excellent hole transport characteristics, in particular, capable of stably and efficiently capturing and transferring holes. In addition, since the hole mobility in and between molecules is improved, the oxidation of the molecule is further suppressed, and further improvement in durability is expected.

[0122] In the hole transport material of (6)(1), it is preferable that it is represented by the following general formula (2). [ka]

[0123] In the hole transport material according to the present embodiment, tetrakis-4-methoxyphenylcarbazole having a planar structure is introduced into the D portion, a thiophene oligomer structure in which three thiophenes are linearly linked into the A portion is constructed, and a hexyl group is introduced as a substituent, thereby improving the maintenance of the planar structure of the molecule and the ease of stacking between molecules. This makes the π conjugation between DAD in the molecule even smoother, and the push-pull effect in the molecule can be appropriately controlled, thereby further improving the charge transfer characteristics. In addition, the hole transport performance is further improved by appropriate stacking between the hole transport materials. This makes it possible to provide a hole transport material having excellent hole transport characteristics that can capture and transfer holes stably and efficiently. In addition, since the hole mobility in and between molecules is improved, the oxidation of the molecule is further suppressed, and further improvement in durability is expected.

[0124] (7) A solar cell 10 using the hole transport material of (1), comprising: a substrate 2 having a transparent conductive film 22; a blocking layer 3 that delivers electrons to the transparent conductive film 22 and prevents reverse electron transfer; a power generation layer 4 formed by stacking a perovskite layer 44 that is excited by light to generate the electrons on a porous semiconductor 41; and a hole transport layer 5 through which holes generated from the perovskite layer 44 pass and which contains the hole transport material, stacked in this order as a laminate 11; and an electrode 6 composed of a photoelectrode 61 that emits the electrons via the transparent conductive film 22, and a counter electrode 62 provided on the surface of the hole transport layer 5.

[0125] The solar cell 10 according to this embodiment includes a hole transport layer 5 formed using the hole transport material according to this embodiment having excellent properties as described above. In particular, the hole transport material according to this embodiment has excellent hole transport properties that can capture and move holes stably and efficiently. In particular, the hole transport material according to this embodiment has a large push-pull effect in its molecule, exhibits excellent intramolecular charge transfer properties, and can exhibit excellent hole transport properties. In addition, as described above, the hole transport material according to this embodiment has excellent light absorption properties and also has excellent properties in terms of durability. Therefore, the solar cell 10 according to this embodiment uses a hole transport material having excellent properties as the hole transport layer 5, thereby improving the photoelectric conversion efficiency, thereby improving the cell performance, and further improving the durability of the solar cell 10.

[0126] In addition, when conventional spiro-OMeTAD and LD29, etc., described in the above [Prior Art] section are used as hole transport materials, LiTFSI is generally added as a dopant having a function of improving hole transport efficiency. However, there are problems in terms of durability, such as the lithium ions contained in LiTFSI diffusing out of the hole transport layer 5 and the solar cell efficiency decreasing over time due to the strong hygroscopicity of LiTFSI itself. In the solar cell 10 according to the present embodiment, the durability of the solar cell 10 can be improved by adding TPFB instead of LiTFSI. This is thought to be because the molecular size of the cation part of TPFB is large, making it difficult to diffuse, and TPFB itself does not have hygroscopicity.

[0127] Furthermore, as described above, the hole transport material according to the present embodiment does not require expensive reagents or complicated processes and can be synthesized inexpensively and simply. By using the hole transport material according to the present embodiment, which is thus cost-effective, it is possible to reduce the price of the solar cell 10 according to the present embodiment.

[0128] [Other embodiments] In the above embodiment, a perovskite solar cell 10 is shown as an example of the solar cell 10 using the hole transport material according to this embodiment, but this hole transport material may also be used in devices using OPV (organic thin-film solar cell), organic electroluminescence (EL), organic semiconductors, and the like. [Industrial Applicability]

[0129] The present invention can be used as a hole transport material for use in perovskite solar cells 10 and the like that include a perovskite compound formed from an organic and inorganic hybrid compound. [Explanation of symbols]

[0130] 2. Board 3 Blocking Layer 4 Power generation layer 5. Hole transport layer 6 electrodes 10. Solar Cells 11 Laminate 21 Transparent substrate 22 Transparent conductive film 41 Porous Semiconductors 44 Perovskite layer 61 Photoelectrode 62 Counter electrode

Claims

1. A hole transport material having a donor-acceptor-donor (DAD) structure represented by the following general formula (1): 【Chemistry 1】 [In general formula (1), The two D regions are regions having the same structure, Each D moiety has a structure selected from the following groups (I), (II), (III), (IV), and (V): 【Chemistry 2】 (In group (I), X and Y are each independently an integer of 0, 1, or 2. R 1 is -H, -C n H 2n+1 , -O-C n H 2n+1 , and -S-C n H 2n+1 where n=an integer from 1 to 8; R 3 is -H, -C n H 2n+1 , -O-C n H 2n+1 , and -S-C n H 2n+1 where n=an integer from 1 to 8; However, R 1 and R 3 is not simultaneously -H, R 2a1 , R 2a2 , R 2b1 , and R 2b2 are each independently -H, -F, or -CF 3 where R 2a1 and R 2a2 At least one of R is -H, 2b1 and R 2b2 At least one of is -H.) 【Chemistry 3】 (In group (II), X and Y are each independently an integer of 0, 1, or 2. R 1 is -H, -C n H 2n+1 , -O-C n H 2n+1 , and -S-C n H 2n+1 where n=an integer from 1 to 8; R 3 is -H, -C n H 2n+1 , -O-C n H 2n+1 , and -S-C n H 2n+1 where n=an integer from 1 to 8; However, R 1 and R 3 is not simultaneously -H, R 2a1 and R 2a2 are each independently -H, -F, or -CF 3 where R 2a1 and R 2a2 At least one of is -H, R 4 is -H, -C n H 2n+1 , -O-C n H 2n+1 , and -S-C n H 2n+1 where n is an integer from 1 to 8; Y is 1 or 2, and R 5 If present, R 5 is introduced at the 3- or 4-position of the thiophene ring in group (II), and -H and -C n H 2n+1 where n is an integer from 1 to 8. 【Chemistry 4】 【Chemistry 5】 【Chemistry 6】 (In group (III), group (IV), and group (V), X and Y are each independently an integer of 0, 1, or 2; Two R's D each independently has a structure represented by the following group (I'): 【Chemistry 7】 (In the group (I'), X' and Y' are each independently an integer of 0, 1, or 2. R 1 ´ is -H, -C n H 2n+1 , -O-C n H 2n+1 , and -S-C n H 2n+1 where n=an integer from 1 to 8; R 3 ´ is -H, -C n H 2n+1 , -O-C n H 2n+1 , and -S-C n H 2n+1 where n=an integer from 1 to 8; However, R 1 ´ and R 3 ´ is not simultaneously -H, R 2a1 ', R 2a2 ', R 2b1 ', and R 2b2 ' are each independently -H, -F, or -CF 3 where R 2a1 ´ and R 2a2 At least one of R′ is —H, 2b1 ´ and R 2b2 ' At least one of them is -H.) In general formula (1), Z is a repeating unit which is an integer from 2 to 11; R A1 and R A2 are each independently -H or -C m H 2m+1 group, where m=an integer from 1 to 12; For each Z repeating units in (), A1 and R A2 may be the same or different.

2. All R in the Z repeating units in () A1 Ha-C m H 2m+1 group, and all R A2 is -H, or all R in the Z repeating units in () A1 is -H, and all R in the Z repeating units in () A2 Ha-C m H 2m+1 The hole transport material of claim 1 , wherein

3. R A1 and R A2 Ga-C m H 2m+1 When selecting a group, -C m H 2m+1 2. The hole transport material of claim 1, wherein the group is an n-hexyl group.

4. 2. The hole transport material of claim 1, wherein Z is 3 or 5.

5. 2. The hole transport material of claim 1, wherein the D moiety is tetrakis-4-methoxyphenylcarbazole.

6. The hole transport material according to claim 1 , represented by the following general formula (2): 【Chemistry 8】

7. A solar cell using the hole transport material according to any one of claims 1 to 6, A substrate having a transparent conductive film; a blocking layer that transfers electrons to the transparent conductive film and prevents reverse electron transfer; a power generation layer formed by laminating a perovskite layer, which is excited by light to generate the electrons, on a porous semiconductor; a hole transport layer through which holes generated from the perovskite layer pass and which has the hole transport material; and a photoelectrode that emits the electrons through the transparent conductive film, and an electrode that is composed of a counter electrode provided on a surface of the hole transport layer.

Citation Information

Patent Citations

  • Hole transport material and solar cell employing hole transport material

    JP2023046046A